2019
DOI: 10.1055/s-0039-1695741
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization and Payer Cost Analysis of Robotic Arm Assisted Total Knee Arthroplasty at 30, 60, and 90 Days

Abstract: This study performed a health care utilization analysis between robotic arm assisted total knee arthroplasty (rTKA) and manual total knee arthroplasty (mTKA) techniques. Specifically, we compared (1) index costs and (2) discharge dispositions, as well as (3) 30-day (4) 60-day, and (5) 90-day (a) episode-of-care costs, (b) postoperative health care utilization, and (c) readmissions. The 100% Medicare Standard Analytical Files were used for rTKAs and mTKAs performed between January 1, 2016, and March 31, 2017. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
0
40
1
Order By: Relevance
“…There were seven clinical studies reporting the functional outcomes following RATKA compared to mTKA (Table 5) [19,23,28,30,31,35,49]. Different outcome scores were utilised across the included studies, with the Knee Society Table 1 Studies included in the systematic review according to how they were identified, when they were published, design, patient demographics, follow up and type of implant [23,28].…”
Section: Functional Outcomes (Level Of Evidence: Good)mentioning
confidence: 99%
“…There were seven clinical studies reporting the functional outcomes following RATKA compared to mTKA (Table 5) [19,23,28,30,31,35,49]. Different outcome scores were utilised across the included studies, with the Knee Society Table 1 Studies included in the systematic review according to how they were identified, when they were published, design, patient demographics, follow up and type of implant [23,28].…”
Section: Functional Outcomes (Level Of Evidence: Good)mentioning
confidence: 99%
“…in utilization of ED when comparing raTKA to mTKA in an analysis of 3,114 Medicare patients. 19 A separate study of Medicare patients found a 33% reduction in 90-day readmission rate comparing raTKA with mTKA. 4 Malkani et al recently reported a 4.5-fold decrease in rates of manipulation for raTKA compared with mTKA.…”
Section: Discussionmentioning
confidence: 99%
“…Case Reports in Orthopedics that robotic arm-assisted THA improved accuracy for both acetabular abduction angles, as well as acetabular anteversion, and demonstrated lower dislocation rates, when compared to manual THA [12][13][14][15]. Finally, RATKA has shown very promising short-term results [8]. In this present paper, we described the first revision from UKA to TKA with the off-label utilization of the robotic arm-assisted arthroplasty platform enhanced with a single-stage manual intervention.…”
mentioning
confidence: 82%
“…The most significant haptic tactile system is the Robotic Arm Interactive Orthopedic MAKO Stryker (RIO; MAKO Stryker, Fort Lauderdale, Florida) system, counting over 700 systems, in use, worldwide. The potential for improving surgical outcomes with the use of the robotic arm-assisted arthroplasty system has already been documented [1,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%